THE IMPACT OF PARENT/FAMILY INVOLVEMENT ON STUDENT’S LEARNING OUTCOMES - Kaukab, SyedaRakhshanda (International Journal of Research -GRANTHAALAYAH, 2016)
The significance of parental involvement, commitment and active participation in children’s education has been documented extensively in recent years across the globe specifically in Europe and the United States. However, it was noted through literature review that currently this is a sparsely researched area for South East Asia. Therefore, the researcher selected this topic to explore the impact of involvement of parents in schools on the educational development of the children. This research study has been conducted to examine the impact of parent or family involvement in the learning outcomes of their children in multiple directions. The research was conducted in five towns of Karachi city. The academic performances of 20 secondary school students from each of the 5 towns, of boys and girls from public and private sectors, were recorded. Schools from each of the five towns were selected through simple random sampling. Two parents and two teachers from each school were interviewed through structured and unstructured questionnaire using survey method as a tool for data collection.